Does the design of the NHS Diabetes Prevention Programme intervention have fidelity to the programme specification? A document analysis. Issue 8 (3rd January 2020) - Hawkes, R. E.; Cameron, E.; Bower, P.; French, D. P.
Abstract: Aims: To assess fidelity of the Healthier You: NHS Diabetes Prevention Programme (NHS‐DPP), a behavioural intervention for people in England at high risk of developing type 2 diabetes, to the specified programme features. Methods: Document analysis of the NHS‐DPP programme specification, including National Institute for Health and Care Excellence (NICE) PH38 diabetes prevention guidance. This was compared with the intervention design (framework response documents and programme manuals) from all four independent providers delivering the NHS‐DPP. Documents were coded using the Template for Intervention Description and Replication framework (describing service parameters) and the Behaviour Change Technique Taxonomy v1. Results: Providers demonstrated good fidelity to service parameters of the NHS‐DPP. The NHS‐DPP specification indicated 19 unique behaviour change techniques. Framework responses for the four providers contained between 24 and 32 distinct behaviour change techniques, and programme manuals contained between 23 and 45 distinct behaviour change techniques, indicating variation in behaviour change content between providers' intervention documents. Thus, each provider planned to deliver 74% of the unique behaviour change techniques specified, and a large amount of behaviour change content not mandated. Conclusions: There is good fidelity to the specified service parameters of the NHS‐DPP; however, the four providers planned to deliver approximately three‐quarters of behaviour change techniques specified by the NHS‐DPP. Given that behaviour change techniques are the 'active ingredients' of interventions, and some of these techniques in the programme manuals may be missed in practice, this highlights possible limitations with fidelity to the NHS‐DPP programme specification at the intervention design stage. What's new?: The National Health Service (NHS) Diabetes Prevention Programme (NHS‐DPP) is a behavioural intervention for adults in England at risk of developing type 2 diabetes. This is the first fidelity evaluation and first known assessment of the behaviour change technique content of a national intervention. The NHS‐DPP intervention design demonstrated good fidelity to the service parameters itemized in the programme specification, but programme manuals included only 74% of the specified behaviour change techniques. As behaviour change techniques are active ingredients that produce behaviour change, this highlights possible limitations with fidelity to the NHS‐DPP programme specification and dilution of likely effect in NHS‐DPP delivery.